DEVELOPMENT OF COMMUNICATIVE COMPETENCE OF STUDENTS IN THE PROCESS OF TEACHING THE UZBEK LANGUAGE - Jurayeva Turgunoy Umarjonovna (American Journals, 2024)
This article cites the emergence and application of the term communicative competence, as well as ideas about the role and importance, goals of communicative competence in students in the process of teaching the Uzbek language. At the same time, the opinions of scientists were added.
Keywords: competence, communicative competence, educational process, student activities, competence, professional competence, pedagogical competence, educational effectiveness, competitive personnel, oral speech, literary language norms, worldview extension, educational system, ability, higher education system, pedagogical activity, competence, knowledge.